2013
DOI: 10.1137/120884316
|View full text |Cite
|
Sign up to set email alerts
|

On the Number of Hamilton Cycles in Sparse Random Graphs

Abstract: Abstract. We prove that the number of Hamilton cycles in the random graph. Furthermore, we prove the hitting-time version of this statement, showing that in the random graph process, the edge that creates a graph of minimum degree 2 creates ln n e n (1+o(1)) n Hamilton cycles a.a.s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 35 publications
(62 reference statements)
4
33
0
1
Order By: Relevance
“…In comparison, in the Erdős–Rényi random graph model G n,p , where each edge appears independently with probability p , the expected number of Hamiltonian paths is about n when pen, but Hamiltonian paths don't appear until plognn. Furthermore, for Hamiltonian cycles in the random graph process, at the moment Hamiltonicity is achieved, the number of Hamiltonian cycles jumps from 0 to [(1+o(1))logne]n, as shown recently by Glebov and Krivelevich (improving an earlier result of Cooper and Frieze ). It may therefore come as a surprise that random edge orderings often have Hamiltonian paths, despite the extremely low expected value.…”
Section: Introductionsupporting
confidence: 58%
“…In comparison, in the Erdős–Rényi random graph model G n,p , where each edge appears independently with probability p , the expected number of Hamiltonian paths is about n when pen, but Hamiltonian paths don't appear until plognn. Furthermore, for Hamiltonian cycles in the random graph process, at the moment Hamiltonicity is achieved, the number of Hamiltonian cycles jumps from 0 to [(1+o(1))logne]n, as shown recently by Glebov and Krivelevich (improving an earlier result of Cooper and Frieze ). It may therefore come as a surprise that random edge orderings often have Hamiltonian paths, despite the extremely low expected value.…”
Section: Introductionsupporting
confidence: 58%
“…This lemma conveniently summarizes the application of the Ore‐Ryser theorem and Egorychev‐Falikman theorem to give a lower bound for the number of 1‐factors in a pseudorandom almost‐regular digraph. (We remark that the statement of , Lemma 4] is for oriented graphs, but the proof applies equally well in the setting of arbitrary directed graphs.) Lemma Let D be a directed graph on [n] (with loops allowed), and consider some r=rfalse(nfalse)loglogn.…”
Section: Proof Outline and Ingredientsmentioning
confidence: 99%
“…lower bound on the total number of 1‐factors in D* (in Lemma 6 in the next section). This will be accomplished with a greedy matching argument combined with the following lemma of Glebov and Krivelevich , Lemma 4]. This lemma conveniently summarizes the application of the Ore‐Ryser theorem and Egorychev‐Falikman theorem to give a lower bound for the number of 1‐factors in a pseudorandom almost‐regular digraph.…”
Section: Proof Outline and Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the random/pseudo-random setting, building on ideas of Krivelevich [25], in [17] Glebov and Krivelevich showed that for p ≥ ln n+ln ln n+ω (1) n and for a typical G ∼ G(n, p) we have h(G) = (1 − o(1)) n n!p n . That is, the number of Hamilton cycles is, up to a sub-exponential factor, concentrated around its mean.…”
Section: Introductionmentioning
confidence: 99%